Sharing Goods? Yuck, No! An Investigation of Consumers' Contamination Concerns About Access-Based Services. (August 2019) - Hazée, Simon; Van Vaerenbergh, Yves; Delcourt, Cécile; Warlop, Luk
Although access-based services (ABS) offer many benefits, convincing consumers to use these service innovations remains challenging. Research suggests that contamination concerns are an important barrier to consumer adoption of ABS; they arise when a person believes someone else has touched an object and transferred residue or germs. However, systematic examination of this phenomenon is lacking. We conduct four experiments to determine (1) the impact of contamination concerns on consumer evaluations of ABS, (2) when such concerns become salient in ABS, and (3) how ABS providers can reduce these concerns. The results reveal that consumers experience more contamination concerns about objects used in proximity to their bodies, especially when those objects are shared with unfamiliar users, and that such concerns negatively influence their evaluations of ABS. Consumers also exhibit less contamination concerns about ABS that have high brand equity because of their elevated stereotype-related perceptions of the competence of those users. Firms' advertisements depicting physical contact between shared objects and other users negatively influence ABS evaluations by consumers whose contamination concept is activated. This article provides insights for developing product, branding, and communication strategies to reduce consumers' contamination concerns and maximize ABS adoption.